Determining the radiation use efficiency of potato using sunshine hour data: a simple and costless approach - Suman Samanta (Spanish Journal of Agricultural Research, 2020)
Aim of study: Radiation parameters and photoperiod influence potato biomass and tuber yield significantly. Lack of instrument facilities in developing countries is the main hindrance to estimate global solar radiation (GSR) and radiation use efficiency (RUE). Considering these facts, an experiment was conducted to estimate light extinction coefficient (K) and RUE using a simple but indirect approach that can be implied in any location lacking sophisticated instruments.